La familia y su incidencia en el desarrollo socio-afectivo de los niños de primer año de educación básica de la escuela fiscal “Cuarto Centenario nº1” de la ciudad de Loja periodo 2009-2010 - Narváez Ponce, Piedad Elizabeth (2014)
This research refers to: FAMILY AND ITS IMPACT ON THE SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN OF FIRST YEAR OF BASIC EDUCATION SCHOOL FISCAL "FOURTH CENTENARY No. 1" Loja CITY PERIOD 2009-2010. For this, the following objective was raised: Contribute to this investigation for the family aware of the importance of their roles to enable develop socially and emotionally fully Children First-Year Basic Education Public School Children "Cuarto Centenario No. 1 "of the City of Loja. The methodology used for this research was taken as the reference population consisting of parents and teachers in the first year of basic education school Cuarto Centenario No. !; using the following methods: Scientist enabled through theory research and analyze the information on the reality of the subject matter; the inductive method yielded information on the actual facts up to determine the problem to be investigated; synthetic analytical method was used for the verification of the objectives and reach conclusions; and statistical-descriptive method that I use in the implementation of the instruments. Besides the techniques and instruments are used as: a survey of teachers and parents for information about the family and their impact on the socio-emotional development, The most important results suggest: that the family influences by 100% in the socio-emotional development of children from the school "Cuarto Centenario No. 1, considering that the family is the core or backbone of child training to develop in the society.